Climate change science and policy - Schneider, Stephen Henry; Rosencranz, Armin; Mastrandrea, Michael D.; Kuntz-Duriseti, Kristin (Island Press, 2010)
In many ways, this volume supersedes the Fourth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC). Many important developments too recent to be treated by the 2007 IPCC documents are covered here. This book considers not only the IPCC report, but also results of the UN Framework Convention on Climate Change held in Bali in December 2007, as well as even more recent research data. Overall, Climate Change Science and Policy paints a direr picture of the effects of climate change than do the IPCC reports. It reveals that climate change has progressed faster than the IPCC reports anticipated and that the outlook for the future is bleaker than the IPCC reported. --from publisher description.